THE EULER NUMBER FROM THE DISTANCE FUNCTION - Gual-Arnau, Ximo (Image Analysis and Stereology, 2013)
We present a new method to obtain the Euler number of a domain based on the tangent counts of concentric spheres in ℝ³ (or circles in ℝ², with respect to the center O, that sweeps the domain. This method is derived from the Poincaré-Hopf Theorem, when the index of critical points of the square of the distance function with respect to the origin O are considered.